The Lawyer’s Professional Duty to Encourage Respect for—and to Improve—the Administration of Justice: Lessons from Failures by Attorneys General - Martin, Andrew (Ottawa Law Review / Revue de droit d’Ottawa)

(untitled) (Ottawa Law Review / Revue de droit d’Ottawa, 2022)
The lawyer’s duty to encourage respect for the administration of justice remains largely amorphous and abstract. In this article, I draw lessons about this duty from historical instances in which Attorneys General inappropriately criticized judges. Not only are Attorneys General some of the highest-profile lawyers in the country, but they also face unique tensions and pressures that bring their duties as lawyers into stark relief. I focus on the two instances where law societies sought to discipline Attorneys General for such criticism of judges, as well as a more recent instance in which no discipline proceedings were pursued. I also consider the obligations of Attorneys General when other Ministers inappropriately criticize judges. I conclude that a lawyer must take all reasonable steps in the circumstances to confirm the factual and legal accuracy of any criticism of the judiciary; that law societies should allow reasonable but defined latitude for public criticism of judges; and that, where a client inappropriately criticizes the judiciary, their lawyer must make good-faith efforts to urge the client to discontinue and apologize for such criticism—and if those efforts are unsuccessful, the lawyer must repudiate that criticism themselves or withdraw.